Study on the Deformation Characteristics of Railway Subgrade Structures Induced by Groundwater Level Changes - Baolong Li; Lulu Jiang; Dongli Wang; Yi Yin; Yupeng Shen; Yunxi Han (Advances in Civil Engineering)
The groundwater extraction will lead to a drop in water level, causing a change in the distribution of additional stress in the strata. This phenomenon leads to uneven settlement of the railway subgrade. In severe cases, this could threaten the safe operation of trains. Therefore, the degree and main factors influencing groundwater extraction in the settlement of the railway subgrade need to be determined through research. Based on railway subgrade engineering, the first step involved monitoring the settlement resulting from groundwater extraction during the spring irrigation period. Following this, the settlement characteristics of the subgrade structure were analysed. Subsequently, based on the Biot consolidation theory of the soil, a numerical simulation model was established to study the threshold parameters of the groundwater extraction on site. Finally, the primary and secondary relationships of the influencing factors must be clarified. The research results show that: (1) According to the monitoring data, groundwater extraction resulted in a subgrade subsidence of 15.2 mm, exceeding the prescribed threshold, affecting the engineering quality. (2) By the numerical simulation results, the distance parameter of the wells is the most significant factor affecting the deformation of the subgrade, followed by the quantity of extraction. So, the distance between the wells and the tracks should be kept at more than 150 m; the pumping volume should not exceed 1500 m3/day. (3) Using horizontal jet grouting piles to reinforce the subgrade can reduce the maximum uneven deformation from 18.14 to 7.86 mm, an effective settlement control measure.